Deep neck space abscesses in children below 5 years of age and their complications. (June 2018) - Jain, Avani; Singh, Ishwar; Meher, Ravi; Raj, Anoop; Rajpurohit, Pragya; Prasad, Purodha
Abstract: Objectives: To study the outcomes and complications of deep neck space abscesses in children less than 5 years of age over a period of 15 years. Methods: A retrospective analysis of children less than 5 years of age with deep neck space abscesses over a 15-year period was conducted at a tertiary care centre in India. Patients were evaluated with respect to the clinical, radiological and laboratory findings. All patients underwent surgical incision and drainage of the abscess and pus cultures were obtained. The incidence of complications was recorded. The collected data was tabulated and statistical analysis was done. Results: A total of 510 children less than 5 years of age were identified who were admitted for deep neck space abscess over a 15-year period. The mean age was 23.6 months. The most common organism isolated in the pus was Staphylococcus aureus (21%). The incidence of methicillin resistant S. aureus (MRSA) was 9%. Complications were reported in 10% patients. Conclusion: Paediatric deep neck abscesses can be managed with prompt surgical management and intravenous antibiotics. Children less than 2 years of age, and those with multiple abscesses or retropharyngeal abscess were more prone to complications.